Comparative Study of a Cybersecurity Curriculum To Support Digital Transformation in The Public Sector - Dhoni Kurniawan; Ratih Mumpuni Arti (Iapa Proceedings Conference, 2020)
The Covid 19 pandemic that has occurred in all parts of the world since early 2020 has forced all humans to follow digital transformation. This momentum is considered good for the acceleration of digital transformation, which since the issuance of Presidential Decree Number 95 of 2018 has begun to be initiated. Digital transformation marks a radical rethinking of how an organization uses technology, people and processes to fundamentally change business performance. Digital transformation occurs in the economic, social and public sphere with the aim of creating innovation, encouraging inclusiveness and increasing efficiency and productivity. Although it is absolutely related to digital technology, digital transformation is not just technology but also takes into account other elements such as infrastructure, policies, leadership, digital literacy, mindset, data, research and cybersecurity. Cybersecurity is a crucial prerequisite because interconnection in the digital world demands data privacy and information security. In fact, the demands of cybersecurity in digital transformation are not matched by human resources who are experts in the cyber field. APTIKOM states that each year in Indonesia it only manages to produce 40 thousand - 50 thousand bachelors of information technology competence, while the need is predicted to reach 600 thousand people per year. At the higher education level, the curriculum in cybersecurity study programs tends to focus on technical areas only. Even though. Cybersecurity is a complex matter that requires a multidisciplinary approach such as experts in regulation and policy, governance and information security risk management, and so on. This research is a qualitative descriptive study. The author uses a comparative method to compare the cybersecurity curriculum in Indonesia with the Netherlands, which has a multi- disciplinary cybersecurity curriculum. So that we get multidisciplinary curriculum recommendations that can be applied in the cybersecurity curriculum in Indonesia.